2021
DOI: 10.17576/jkmjc-2021-3701-16
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Infografik dalam Menangani Persepsi Negatif Netizen Terhadap Institusi Zakat di Malaysia

Abstract: Utilizations of Infographics for Dissatisfied Netizens towards Zakat Institutions in Malaysia ABSTRACT Resentment towards zakat institutions in Malaysia is viral issues among netizens. Netizens’ dissatisfaction towards the institutions includes proportions of zakat distribution, service quality, consumer attitude and trust in the institution. Therefore, this paper aims to explore the potentials of infographics as an effective communication tool to provide accurate information and to address issues and concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Abidin et al ( 2014) have identified management and user perceptions about the importance of leveraging internet use by zakat institutions as the primary communication medium, especially regarding public trust and recognition. The development of multimedia materials such as infographics is very much needed; some of the things contained in infographics need to be followed by current issues and initiatives that have been carried out by zakat institutions (Nawi et al 2021).…”
Section: Tree Map Analysis In Journal Malaysian Zakatmentioning
confidence: 99%
“…Abidin et al ( 2014) have identified management and user perceptions about the importance of leveraging internet use by zakat institutions as the primary communication medium, especially regarding public trust and recognition. The development of multimedia materials such as infographics is very much needed; some of the things contained in infographics need to be followed by current issues and initiatives that have been carried out by zakat institutions (Nawi et al 2021).…”
Section: Tree Map Analysis In Journal Malaysian Zakatmentioning
confidence: 99%
“…To the best of our knowledge, little work has been done in understanding the factors behind social media adoption in zakat institutions and its impact. It is suggested that the use of social media by zakat institutions in Malaysia is still at an early stage and has not been used optimally (Nawi et al , 2021). A literature review found that academic work on social media and zakat institutions is scattered in multiple themes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the face-to-face interviews approach was changed to the online meetings approach using the Zoom application [3]. In this research, the phenomenon of social media adoption in zakat institutions is at an early stage of adoption (Nawi et al , 2021). The series of interviews with zakat institutions was useful for exploring and understanding respondents’ viewpoints on zakat institutions’ adoption of social media applications.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The importance of personal data protection is in line with Islamic teachings. Islam attaches great importance to the protection of personal data because it is included in the right to privacy (Hayat 2007;Nawi et al 2021). This is evidenced in surah al-Hujurat verse 12 and surah an-Nur verse 27.…”
Section: Artificial Intelligence Policies and Islamic Regulationsmentioning
confidence: 99%